The Intelligence, Emotional, Spiritual Quotients and Quality of Managers. - Juhary, Ali; Ali Bambang, Bemby; Ilham, Sentosa (2013)
Intelligence, emotional, and spiritual quotients (IESQ) has been predicted to escalate with the increase of personal quality of corporate managers. In line with the enhancement of personal quality, it has been estimated that internal locus of control would also amplify. This study examined the drivers of personal quality of corporate managers based on the examination of intelligence, emotional, and spiritual quotients (IESQ) and mediated by internal locus of control. Data were collected from 237 stated owner enterprises managers via questionnaires. The analysis produced structural models of personal quality predicted by IESQ and mediated by internal LOC. It shows that hypothesized model created three significant positive direct (IESQ) and indirect (internal LOC) impacts of predictors to personal quality of managers. For mediating effect of internal LOC on each hypothesized path, this study found partial mediating effects of internal LOC. The structural model achieved the highest SMC (R2), explaining 65.6% of internal locus of control and 76.2% variance of the personal quality of managers. This study confirmed a significant positive direct relationship between the harmonies of IESQ to personal quality. This study found most of managers have a good standard of EQ and SQ rather than IQ. In this case, the application of EQ in a workplace depended on the person, whether he or she could place him or herself in gathering with others. Spiritual quotient seemed placed highest portion when mediated with locus of control. As we know that internal LOC is a strong feeling that pushes someone to do something correctly.